2011
DOI: 10.3233/jad-2011-101641
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelets Tau: A Potential Peripheral Marker for Alzheimer's Disease

Abstract: Platelets are a major peripheral reservoir of the amyloid-β protein precursor, so they have been considered as a potential biological marker of Alzheimer's disease (AD). Here, it is demonstrated that tau protein is also present in platelets and that the levels of oligomeric species of this protein could serve as a novel and reliable biological marker for AD. Blood samples were obtained from 15 AD patients and 10 paired-age controls and platelets were separated via differential centrifugation. The purity of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 26 publications
3
58
0
3
Order By: Relevance
“…The increased platelet GSK3β activity was reported in patients in early AD stages [29]. The definite role of platelet GSK3β is still unclear, but there is evidence of its involvement in the regulation of platelet activation and τ forms in AD [28][29][30]. The potential of molecular changes related to τ and amyloid pathology in platelets as diagnostic biomarkers is promising and awaits further investigation.…”
Section: Reviewmentioning
confidence: 99%
“…The increased platelet GSK3β activity was reported in patients in early AD stages [29]. The definite role of platelet GSK3β is still unclear, but there is evidence of its involvement in the regulation of platelet activation and τ forms in AD [28][29][30]. The potential of molecular changes related to τ and amyloid pathology in platelets as diagnostic biomarkers is promising and awaits further investigation.…”
Section: Reviewmentioning
confidence: 99%
“…Li et al [42] first characterized the expression of the Tau protein in platelets, and further showed that the phosphoepitope thr-212 is dephosphorylated as a consequence of the inhibition of GSK3B in platelet homogenates. A recent study from Neumann et al [11] showed that several molecular species of Tau are present in platelets, and AD patients have a different proportion of the various forms of Tau as compared to controls. In fact they found several immunoreactive fractions ranging from approximately 60 to 240 kDa and, notably, that high molecular weight fractions of Tau (110-130 kDa) are increased in AD patients as compared with controls.…”
Section: Glycogen Synthase Kinase and Taumentioning
confidence: 99%
“…In addition, the ratio between high molecular weight and low molecular weight (ranging from 66 to 68 kDa) fractions seems to be significantly increased in AD subjects. The oligomers of the high molecular weight form of Tau may correspond to aggregates of the nearly 60 kDa monomer forms which subsequently decrease since they are consumed when higher order oligomers are being formed in AD [11] .…”
Section: Glycogen Synthase Kinase and Taumentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies are underway to validate PET images that differentiate stages of AD and controls. As a complementary approach, we have studied tau in cerebrospinal fluid (CSF) and also in peripheral blood platelets, providing promising biological non-invasive markers for AD Neumann et al, 2011).…”
Section: Integrated Efforts Toward Prevention Diagnosis and Treatmenmentioning
confidence: 99%